Disaster response and recovery training - Lunde, Diane B., author (Colorado State University. Libraries, 2008)
Presentation used for staff training of Colorado State University Libraries' Metadata and Preservation Services Department.
Keywords: disaster response; disaster planning; Morgan Library; Colorado State University Libraries; disaster recovery; preservation; Emergency management; Disasters; Library materials -- Conservation and restoration; Archival materials -- Conservation and restoration